1988
DOI: 10.1111/j.1471-4159.1988.tb13225.x
|View full text |Cite
|
Sign up to set email alerts
|

A Similar Calmodulin‐Binding Protein Expressed in Chromaffin, Synaptic, and Neurohypophyseal Secretory Vesicles

Abstract: The presence of calmodulin-binding proteins in three neurosecretory vesicles (bovine adrenal chromaffin granules, bovine posterior pituitary secretory granules, and rat brain synaptic vesicles) was investigated. When detergent-solubilized membrane proteins from each type of secretory organelle were applied to calmodulin-affinity columns in the presence of calcium, several calmodulin-binding proteins were retained and these were eluted by EGTA from the columns. In all three membranes, a 65-kilodalton (63 kiloda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Structural, biochemical, and physiological data are consistent with a crucial role of synaptotagmin in neurotransmitter release (reviewed by DeBello et al, 1993). It is one of the major membrane components of synaptic vesicles (Matthew et al, 1981;Fournier and Trifaro, 1988) and is exclusively expressed in neurons and neuroendocrine cells. Synaptotagmin binds Ca*+ at concentrations in the lo-100 PM range in a phospholipid-dependent manner (Brose et al, 1992) and has been postulated to be the Caz+ sensor which induces exocytosis.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Structural, biochemical, and physiological data are consistent with a crucial role of synaptotagmin in neurotransmitter release (reviewed by DeBello et al, 1993). It is one of the major membrane components of synaptic vesicles (Matthew et al, 1981;Fournier and Trifaro, 1988) and is exclusively expressed in neurons and neuroendocrine cells. Synaptotagmin binds Ca*+ at concentrations in the lo-100 PM range in a phospholipid-dependent manner (Brose et al, 1992) and has been postulated to be the Caz+ sensor which induces exocytosis.…”
mentioning
confidence: 74%
“…Although synaptotagmin's role in the exocytosis of secretory vesicles is not clearly established in neuroendocrine cells (see Shoji-Kasai et al, 1992, andElferink et al, 1993), several laboratories have demonstrated synaptotagmin to be present on chromaffin granules (Matthew et al, 1981;Fournier and Trifaro, 1988;Perin et al, 1990). Furthermore, Walch-Solimena et al (1993 showed that synaptotagmin I is present on large dense core vesicle membranes of the posterior pituitary.…”
Section: Discussionmentioning
confidence: 99%
“…Its site of action is unclear but an action mediated via calmodulindependent protein kinases is unlikely due to its lack of requirement for MgATP. One possible target is the vesicle protein synaptotagmin, which is a component of the SNARE complex (S611ner et al, 1993a), which may be a Ca 2+ receptor in exocytosis (Geppert et al, 1994) and is a known calmodulin-binding protein (Fournier and Trifaro, 1988;Tugal et al, 1991). The ability of synaptotagmin to bind calmodulin is controversial and calmodulin may have an alternative mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible target is the vesicle protein synaptotagmin, which is a Ca 2ϩ -binding protein and also a CaM-binding protein (48,49). Synaptotagmin is likely to be a Ca 2ϩ sensor in the final fusion step of exocytosis (23,24).…”
Section: Camentioning
confidence: 99%